Abnormal interfacial bonding mechanisms of multi-material additive-manufactured tungsten–stainless steel sandwich structure - Yuchen Gu (International Journal of Extreme Manufacturing, 2022)
Tungsten (W) and stainless steel (SS) are well known for the high melting point and goodcorrosion resistance respectively. Bimetallic W–SS structures would offer potential applicationsin extreme environments. In this study, a SS→W→SS sandwich structure is fabricated via aspecial laser powder bed fusion (LPBF) method based on an ultrasonic-assisted powderdeposition mechanism. Material characterization of the SS→W interface and W→SS interfacewas conducted, including microstructure, element distribution, phase distribution, andnano-hardness. A coupled modelling method, combining computational fluid dynamicsmodelling with discrete element method, simulated the melt pool dynamics and solidification atthe material interfaces. The study shows that the interface bonding of SS→W (SS printed on W)is the combined effect of solid-state diffusion with different elemental diffusion rates and grainboundary diffusion. The keyhole mode of the melt pool at the W→SS (W printed on SS)interface makes the pre-printed SS layers repeatedly remelted, causing the liquid W to flow intothe sub-surface of the pre-printed SS through the keyhole cavities realizing the bonding of theW→SS interface. The above interfacial bonding behaviours are significantly different from thepreviously reported bonding mechanism based on the melt pool convection during multiplematerial LPBF. The abnormal material interfacial bonding behaviours are reported for the firsttime